Determination of 15 polycyclic aromatic hydrocarbons in aquatic products by solid‐phase extraction and GC–MS. Issue 10 (3rd April 2018) - Liu, Qiying; Guo, Yuanming; Sun, Xiumei; Hao, Qing; Cheng, Xin; Zhang, Lu
Abstract: We propose a method for the simultaneous determination of 15 kinds of polycyclic aromatic hydrocarbons in marine samples (muscle) employing gas chromatography with mass spectrometry after saponification with ultrasound‐assisted extraction and solid‐phase extraction. The experimental conditions were optimized by the response surface method. In addition, the effects of different lyes and extractants on polycyclic aromatic hydrocarbons extraction were discussed, and saturated sodium carbonate was first used as the primary saponification reaction and extracted with 10 mL of ethyl acetate and secondly 1 mol/L of sodium hydroxide and 10 mL of n ‐hexane were used to achieve better results. The average recovery was 67–112%. Satisfactory data showed that the method has good reproducibility with a relative standard deviation of <13%. The detection limits of polycyclic aromatic hydrocarbons were 0.02–0.13 ng/g. Compared with other methods, this method has the advantages of simple pretreatment, low solvent consumption, maximum polycyclic aromatic hydrocarbons extraction, the fast separation speed, and the high extraction efficiency. It is concluded that this method meets the batch processing requirements of the sample and can also be used to determine polycyclic aromatic hydrocarbons in other high‐fat (fish, shrimp, crab, shellfish) biological samples.